The handbook of classroom discourse and interaction - Markee, Numa (Wiley-Blackwell, 2015)
"The Handbook of Classroom Discourse and Interaction is an authoritative reference work exploring the latest research, methodologies, and theories related to classroom language, teaching, and learning"-- Provided by publisher
Keywords: Language and languages -- Study and teaching.; Conversation analysis -- Study and teaching.; Interaction analysis in education.; Classroom environment.; Classroom learning centers.; elektronické knihy; electronic books